Optimalisasi Hak Ekonomi Nanas Tangkit Baru Jambi Sebagai Produk Indikasi Geografis - Nickyta Sidabutar, Emi; Suryahartati, Dwi; Oktaviarni, Firya (Zaaken: Journal of Civil and Business Law, 2024)
Geographical indication is part of the Intellectual Property regulated in the Law Number 20 of 2016 on Trademarks and Geographic Indications, Tangkit pineapple is a typical Pineapples Village of New Tangit district of Muaro Jambi which must be protected in order to obtain legal protection of Geographic Indication. The aim of this research is to identify and analyze the economic benefits for communal communities that are integrated into the MPIG Nanas New Infection Group. To identify the role of the government in optimizing the utilization of Geographical Indications for the new Infection Society. The basic problems in this research are: 1) How the economic benefit for the communal community that is integrated in the new infection MPIG Group is formed. 2) How the government's role in optimising the use of geographical indications for new infected communities. This research uses empirical methods of jurisprudence with data collection techniques using observations, interviews and documentation. The conclusion of the results of the discussion in the research showed that: 1) The form of economic benefits made by the people of the village of Tangkit New to increase the revenue of the region is to manage UMKM or home industry by processing pineapple fruit into various kinds of processed products. 2) The role of the Muaro Jambi Government in optimizing the use of Geographical Indications is to provide support in the provision of guidance and training as well as facility assistance.